REVIEW: THE ROLE OF HERBAL AS A THERAPY FOR ENDOTHELIAL DYSFUNCTION IN CARDIOVASCULAR DISEASES: NARRATIVE REVIEW - Febriana Astuti; Akrom; Rafiastiana Capritasari (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Atherosclerosis, diabetes mellitus, hypertension, and aging are examples of cardiovascular illnesses, the pathogenesis of which is affected by endothelial dysfunction. Many patients with cardiovascular disease already use herbs or combine herbs with medications prescribed by doctors. Herbs have emerged as alternative treatments for health maintenance. Herbs are in increasing demand by patients and health professionals. An overview of the role of herbal plants, their active substances, and their mechanisms of action as therapies for endothelial dysfunction to prevent the worsening of cardiovascular disease is presented in this review. The research was carried out by reviewing published scientific papers using online sources, such as PubMed and Google Scholar. Herbs can be used as a therapy for endothelial dysfunction to prevent the worsening of cardiovascular disease through various mechanisms, including inhibition of oxidative stress through the COX-2 and NOX2 pathways, inhibition of NADPH oxidase, inhibition of ROS formation through Src/EGFR/Akt, and increasing nitric oxide (NO) production by activating eNOS. The benefits and potential of herbal plants in dysfunction therapy to prevent cardiovascular disease need to be further developed for plants that grow widely in Indonesia. Furthermore, it is necessary to develop mechanisms for other targets, such as immunomodulatory therapy, to prevent cardiovascular disease from worsening. Keywords: Herbals, Endothelial Dysfunction, Cardiovascular Disease